Digital Detox and Mental Well-being: Evaluating the Benefits of Reducing Screen Time in the Digital Era - Nehaluddin AHMAD; Norarfan ZAINAL; Hajah Ummi Fa’izah binti Haji Abdul Rahman; Norulaziemah ZULKIFFLE; Zheimie H. ZAMRI (Communications of International Proceedings, 2025)
In the modern age of technology, the common use of electronic devices has caused serious concern about their effect on mental health and overall health. The practice of digital detoxing, or the purposeful reduction or elimination of screen time for a specific interval of time, and its psychological advantages are discussed here. Based on empirical evidence, psychological theory, and specialist opinion, this essay examines how screen time reduction can positively affect mental health outcomes such as lower anxiety levels, better quality sleep, improved productivity, and improved interpersonal relationships. It also reflects on the challenges of using digital detox strategies and concludes by outlining evidence-based interventions and policy proposals to inform healthier digital use strategies. Finally, a digital detox is an effective method of ensuring mental balance in the technological age, offering individuals an interval of time to regain equilibrium, presence, and emotional resilience.
Keywords: Digital Detox; Mental Health; Technologies; Social Media; Psychology.